Peran Kematangan Emosi dalam Mengurangi Somatic Symptom Burden pada Mahasiswa, dengan Stres Sebagai Mediator - Baso, Syahrul Hidayat Putra; Fakhri, Nur Fitriany; Ismail, Ismalandari (FORIKES, 2025)
The academic and social demands experienced by college students have triggered stress, which can impact physical health through the emergence of somatic symptoms. The purpose of this study was to examine the relationship between emotional maturity and somatic symptom burden in college students, with stress as a mediator. The method used in this study was a quantitative study, with 452 active college students aged 17-25 studying in Makassar and its surrounding areas as subjects. Data were collected through questionnaires and analyzed using the Spearman correlation test and the Hayes Macro Process mediation test. The analysis showed that stress played a significant role as a mediator in the relationship between emotional maturity and somatic symptom burden in college students, with a correlation value of 0.0410 and a significance level of 0.000. Furthermore, it was concluded that there is a relationship between emotional maturity and somatic symptom burden in college students mediated by stress, meaning that stress plays a mediator in the relationship between emotional maturity and somatic symptom burden in college students.Keywords: emotional maturity; somatic symptoms; college students ABSTRAK Tuntutan akademik dan sosial yang dialami mahasiswa telah memicu terjadinya stres yang dapat memengaruhi kesehatan fisik dengan munculnya gejala somatis. Tujuan penelitian ini adalah menguji hubungan antara kematangan emosi dan somatic symptom burden pada mahasiswa, dengan stres sebagai variabel mediator. Metode yang digunakan dalam penelitian ini adalah studi kuantitatif dengan subjek penelitian adalah 452 mahasiswa aktif berusia 17-25 tahun yang berkuliah di Kota Makassar dan sekitarnya. Data dikumpulkan melalui pengisian kuesioner, lalu dianalisis menggunakan uji korelasi Spearman dan uji mediasi Process Macro Hayes. Hasil analisis menunjukkan bahwa stres berperan signifikan sebagai mediator pada hubungan kematangan emosi dengan somatic symptom burden pada mahasiswa dengan nilai korelasi sebesar 0,0410 dan taraf signifikansi 0,000. Selanjutnya disimpulkan bahwa ada hubungan antara kematangan emosi dengan somatic symptom burden pada mahasiswa yang dimediasi oleh stres, artinya stres berperan sebagai mediator dalam hubungan antara kematangan emosi dengan somatic symptom burden pada mahasiswa.Kata kunci: kematangan emosi; gejala somatis; mahasiswa